Türk düşüncesi dergisinde Doğu-Batı meselesi - Demir, Esra (My University, 2019)
TÜRK DÜŞÜNCESİ DERGİSİNDE DOĞU-BATI MESELESİCumhuriyet rejimi ile resmi ideolojinin önemli bir unsuru haline gelen pozitivist ve materyalist bir Batılılaşma hareketine yönelik tenkitlerin yer aldığı Türk Düşüncesi dergisi, değişim halinde bulunan Batı’yı doğru anlama çabasında olduğunu savunmaktadır. Tek partili yılların ardından 1953- 1960 yılları arasında, muhafazakâr bir çizgide, Peyami Safa’nın öncülüğünde yayımlanan Türk Düşüncesi dergisinde tartışılma imkânı bulan Doğu ve Batı medeniyetiyle irtibatlı meseleleri değerlendirmek bu çalışmanın temel amacıdır. Türk Düşüncesi dergisinde “Hangi Batı?” sorusu bağlamında, manevi değerlere yönelen Batı’nın temayülüyle paralel; Bergsonizm, mistisizm ve Doğu Batı sentezi Türkiye için çözüm olarak sunulmaktadır. Çalışmamızda Batılılaşma sürecinde Türkiye’nin temel zihniyet problemleri; kültür-medeniyet ayrımı, inkılâp-irtica, din, dil gibi meseleler de tartışılmaktadır. Yakın geçmişimizde muhafazakâr bir dergide yer alan Doğu Batı meselesi, bugünkü tartışmaların seyrini anlamlandırabilmemiz için önem arz etmektedir.

THE QUESTION OF THE EAST-WEST IN TÜRK DÜŞÜNCESİTürk Düşüncesi, issued in the years between 1953 and 1960, was a periodical that provided a critique of the Westernization movement, embracing positivism and materialism, which was also a significant element of the Republican regime and the official ideology. The main objective of the periodical, issued under the guidance of Peyami Safa following the single party rule between the abovementioned years, was to provide analyses concerning the East and West civilizations. Within the context of the question, “Which West?”, Türk Düşüncesi offered a solution for Turkey, on the basis of Bergonism, mysticism, as well as a synthesis between the East and the West, in parallel with the certain tendencies of the Western thought, attending to moral values. The topics in the periodicals centered upon the fundamental problems in the process of the Westernization process, the difference between the notions of culture and civilization, the reforms and reactionism as well as the religion and language. Türk Düşüncesi, which offered a conservative voice at the time, stands as a valuable source to understand both the East-West dichotomy, a question that was a major concern of a conservative periodical, and the discussions that we are still engaged in at the moment.
Keywords: Doğu- Batı; Felsefe ve din; Islamic philosophy; inkılâp; İslam felsefesi; Peyami Safa; Philosophy and religion; sentez; synthesis; The East-West dichotomy; the reforms; Türk Düşüncesi